The Decrease of Anxiety in Secsio Sesaria Mother with "Sayang Bunda" Model - Dhiana Setyorini; Moch. Bahrudin (Jurnal Ners, 2010)
Introduction: Mother with secsio sesaria will find an problem, both a physical and psychological problems. A psychological problem that often happen in mother with secsio sesaria is an Anxiety problem. The aimed of this study was to know the effectiveness of "SAYANG BUNDA" in reducing the anxiety of seccio caesaria mother.Method: Quasy Experimental Pretest-Postest with contol group design was used in this study. The population in this study was mother with electif sectio sesaria who pregnant examinated in Darmo Hospital, William Both Hospital, Suwandi Hospital, Bunda Hospital and Darus Syifa' Hospital of Surabaya. Total sample was 60 people divided into 30 of intervention group and 30 of control. The samples was taken by Quota sampling. The effectiveness of "SAYANG BUNDA" to decrease anxiety was analyzed by using t test (independent samples t-test).Result: The Results of homogeneity test found that between control and intervention groups were homogeneous (p ≥  0.05). The results of this study indicate that there were signi fi cant differences on anxiety between control and intervention group (p = 0.00), the control group had an average higher anxiety than the intervention group after getting "SAYANG BUNDA". Similarly to the level of anxiety, anxiety levels decreased after getting "SAYANG BUNDA" (p = 0.018).Discussion: "SAYANG BUNDA" effective for reducing anxiety in women with secsio sesaria. The implication of this study is health education with "SAYANG BUNDA" can be applied to mothers with planned elective cesarean section at the time of antenatal education.